Mycophenolate mofetil-related colitis in a paediatric patient after kidney transplant - Natalia Oleksik; Monika Głowinkowska; Maria Szczepańska; Katarzyna Bąk-Drabik; Wioletta Jarmużek (Termedia Publishing House, 2022)
Mycophenolate mofetil (MMF) is an immunosuppressive agent, the gastrointestinal side effects of which include abdominal pain, diarrhoea, and vomiting. MMF may also cause symptomatic colitis, although it is a rare condition. We present herein the case of a boy with chronic kidney disease, lasting since the neonatal period, and caused by WT1 gene mutation. The patient developed colitis during an immunosuppressive therapy applied after a kidney transplant. Histopathology of intestinal biopsy specimens revealed features of MMF-related colitis. A modification of the immunosuppressive treatment and the implementation of a nutritional programme to the patient resulted in the disappearance of clinical signs and helped in a gradual body weight gain.